"I am proud to be from Uzbekistan" - Shoniyeva Oyjamol (Zien Journals, 2022)
In this article, respect for the motherland, devotion feelings of gratitude we are talking about. The love of the homeland is infinite and true.
Keywords: Homeland; national value; reforms